Como melhorar o diagnóstico precoce do câncer bucal? - Bandeira, Celso Muller [UNESP]; de Almeida, Adriana Ávila [UNESP]; Carta, Celina Faig Lima; Almeida, Janete Dias [UNESP]; Kaminagakura, Estela [UNESP] (Editora Cubo, 2017)
Objective: Oral squamous cell carcinoma (OSCC) is one of the most common malignant neoplasms, with 300,000 new cases annually diagnosed in the world. Although it appears in the fifth position among men in Brazil, late diagnosis continues to be a leading cause of poor prognosis. We reviewed the literature to evaluate factors that contribute to diagnostic delay in oral cancer considering aspects related to the patient, health team and public health system. Material and Methods: The Medline (PubMed), Scopus, Web of Science and Embase databases were searched in the last 5 years using the following MeSH descriptors: carcinoma, squamous cell; mouth neoplasms; delayed diagnosis. The articles should contain in their objectives factors contributing to the delayed diagnosis of OSCC related to the patient, healthcare professionals and public health system in general. Results: One hundred twenty articles were retrieved and 27 on the delayed diagnosis of oral cancer were eligible. Conclusion: The literature showed that the delay in the diagnosis and treatment of patients with oral cancer could be minimized by providing health information, particularly about risk factors, by improving the training and retraining of physicians and dentists and by improving access to the health system. The communication technologies such as telemedicine, can play a key role in the early diagnosis of oral cancer.
How to improve the early diagnosis of oral cancer?
Keywords: Carcinoma; Delayed diagnosis; Mouth neoplasms; Squamous cell